Evaluation of the Knowledge and Awareness Level of the Pediatric Residents About the Diagnosis, Treatment and Follow-up of Urinary Tract Infection in Children - Fatma Devrim; Dorukhan Besin; Aslı Kantar Özşahin; Betül Pehlivan Zorlu; Özlem Dur; Ebru Yılmaz; Nida Dincel (Trends in Pediatrics)
Objective: In this study, we sought to assess pediatric residents’ level of knowledge about the diagnosis, treatment, and follow-up of urinary tract infection in children.